The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2000
DOI: 10.1021/ie0004491
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Solid Deposits from Thermal Stressing of a JP-8 Fuel on Different Tube Surfaces in a Flow Reactor

Abstract: Thermal stressing of a JP-8 fuel was carried out in an isothermal flow reactor using nickel, stainless steel (316 and 304), Silcosteel, and glass-lined stainless steel tubes at 500 °C wall temperature and 34 atm (500 psig) for 5 h at a liquid fuel flow rate of 1 mL/min. Different length segments along the sample tubes were analyzed to observe the deposit distribution throughout the test section. Temperature-programmed oxidation (TPO) analysis and SEM examination of the stressed tubes showed differences in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
110
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(122 citation statements)
references
References 20 publications
10
110
2
Order By: Relevance
“…In contrast, the series of catalysts Pt/WZ800 x did not present suitable catalytic activity in the process. Maybe, this is because their specific surface area and surface acidity reduced sharply after being calcined at 800 • C. And it is generally accepted that the metal elements (mainly Fe and Ni) of stainless steel tubes may give way to an improvement of RP-3 pyrolysis, while the catalysts coated on the inner surface of tubes inhibited the metal catalysis of the stainless steel tubes [28][29][30]. Furthermore, the pore volume of Pt/WZ800 x decreased while the average pore diameter increased.…”
Section: The Catalytic Performance Of Catalystsmentioning
confidence: 99%
“…In contrast, the series of catalysts Pt/WZ800 x did not present suitable catalytic activity in the process. Maybe, this is because their specific surface area and surface acidity reduced sharply after being calcined at 800 • C. And it is generally accepted that the metal elements (mainly Fe and Ni) of stainless steel tubes may give way to an improvement of RP-3 pyrolysis, while the catalysts coated on the inner surface of tubes inhibited the metal catalysis of the stainless steel tubes [28][29][30]. Furthermore, the pore volume of Pt/WZ800 x decreased while the average pore diameter increased.…”
Section: The Catalytic Performance Of Catalystsmentioning
confidence: 99%
“…7d-f). The dust-like coke is amorphous carbon deposits due to the non-catalytic coking [39,40]. TiN coatings can effectively prevent metal dusting and therefore suppress the related catalytic coking and eliminate the filamentous coke, because the metal substrate has been covered completely by TiN coating above 850°C.…”
Section: The Anti-coking Performance Of Tin Coatingsmentioning
confidence: 99%
“…22 In addition, Eser et al observed that solid deposits were reduced by nearly 90% in a silcosteel reactor relative to that in stainless steel 316 tubes during supercritical thermal stressing of JP-8 (500°C and 3.4 MPa, 1 mL/min for 5 h). 19 Ervin et al found that pyrolytic Industrial & Engineering Chemistry Research ARTICLE deposition was eliminated above 90% in silcosteel during supercritical thermal stressing of Jet A (400À700°C and 3.89À6.31 MPa, 32 mL/min for 4À8 h) and that the formation of pyrolytic deposition was less sensitive to pressure on treated tubes relative to untreated stainless steel tubes. 10 Therefore, surface coating over the stainless steel tube with controllable thickness is taken as an ideal technique to depress the filamentous carbon from metal catalysis ascribed to forming a passive layer, which is a potential technique for resolving the coking issues in advanced aircraft.…”
Section: Introductionmentioning
confidence: 99%